Predictive values of clinical data,molecular biomarkers, and echocardiographic measurements in preterm infants with bronchopulmonary dysplasia - Wang, Huawei; Yan, Dongya; Wu, Zhixin; Geng, Haifeng; Zhu, Xueping; Zhu, Xiaoli (Frontiers in Pediatrics, 2023)
Objective: We aimed to use molecular biomarkers and clinical data and echocardiograms collected at admission to predict bronchopulmonary dysplasia (BPD) in preterm infants with gestational age ≤ 32 weeks. Methods: Eighty-two patients admitted to the Department of Neonatology of the Children’s Hospital of Soochow University between October 1, 2018, and February 29, 2020, were enrolled in this study. Basic clinical data on the perinatal period, echocardiographic measurements, and molecular biomarkers were collected. We used multiple logistic regression analysis to establish an early predictive model for preventing BPD development in preterm infants of gestational age ≤ 32 weeks. Results: The use of caffeine, albumin, gamma globulin; ventilation; days of FiO2 ≥ 40%; oxygen inhalation time; red blood cell suspension infusion volume (ml/kg); and proportion of infants who received total enteral nutrition (120 kcal/kg.d) ≥ 24 d after birth were higher in the BPD group than in the non-BPD group. The levels of hemoglobin, hematocrit, and albumin in the BPD group were significantly lower than those in the non-BPD group. The total calorie intake was significantly lower in the BPD group on the 3rd, 7th, and 14th day after birth than in the non-BPD group (P < 0.05). The incidence rates of patent ductus arteriosus (PDA), pulmonary hypertension, and tricuspid regurgitation were significantly higher in the BPD group than in the non-BPD group (P < 0.05). The serum level of NT-proBNP 24 h after birth was significantly higher in the BPD group than in the non-BPD group (P < 0.05). Serum NT-proBNP levels were significantly higher in infants with severe BPD than in those with mild or moderate BPD (P < 0.05). Conclusion: The tricuspid regurgitation flow rate (m/s), NT-proBNP (pg/ml), ventilator-associated pneumonia, days of FiO2 ≥40% (d), red blood cell suspension infusion volume (ml/kg), and proportion of infants who received total enteral nutrition (120 kcal/kg.d) ≥ 24 d after birth were the most practical factors considered for designing an appropriate model for predicting the risk of BPD.